ANALISIS SUMBER DAYA PERIKANAN LEMURU (Sardinella lemuru Bleeker 1853) DI SELAT BALI (Analysis of the Sardine Oil (Sardinella lemuru Bleeker 1853) Resources in Bali Strait) - Himelda Himelda; Eko Sri Wiyono; Ari Purbayanto; Mustaruddin Mustaruddin (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2011)
Sardine oil (Sardinella lemuru Bleeker 1853) is the one of fish target of fishermen from Banyuwangi and Jembrana who fish in Bali strait. An in-depth study on current utilization rates and over 6 year period is required to obtain information on utilization of the sardine oil. . This study can be used as a guideline in formulating a policy in fishery management to promote sustainable sardine oil resources in Bali Strait. The purposes of this research were to calculate catch per unit effort (CPUE) of fishing gears, determine the standard fishing gears, determine of the production function, and determine feeding habits of sardine oil by analysing the stomach contents. Compared to other fishing gears, CPUE of purse seine has the highest average which made up 332.2032 metric ton per unit. Based on the calculation of the production function, the value of Cmsy was 88,358.71 metric ton per years, and the value of Emsy was 414.601 units. The analysis of the stomach contents showed that sardine oil’s food was plankton which consisted of phytoplankton and zooplankton. During the 6 year period, utilization of sardine oil resources was still allowed, because the highest catch did not exceed Cmsy. However, to sustain the resources, management and regulation in the use of fishing gears, especially purse seine was still needed. It can be done by renewing the joint decree between Governor of East Java and Bali in 1992.Key words: resources analysis, sardine oil fisheries, Bali Strait